Effect of hydrogel stiffness on nucleus pulposus cell phenotypes in vitro and its repairment of intervertebral disc in vivo - CHEN Zehao; LÜ Zhendong; ZHANG Zhen; CUI Wenguo; ZHANG Yuhui (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2023)
Objective·To investigate the effect of hydrogel stiffness on nucleus pulposus cell phenotype and its function in repairing intervertebral disc degeneration in rats.Methods·Methacrylate gelatin (GelMA) hydrogels with different concentrations were constructed. The stiffness of the hydrogels was investigated by using rheological analysis and uniaxial compression test. The microstructure and morphology of the hydrogels were observed by scanning electron microscopy (SEM). Nucleus pulposus cells with normal phenotype were inoculated on the surface of GelMA hydrogels. The biocompatibility of the hydrogel was evaluated by live-dead cell staining and the growth pattern of nucleus pulposus cells on hydrogels with different stiffness was observed with phalloidin staining under microscope. Immunofluorescence staining was performed to examine the nuclear localization of Yes-associated protein (YAP) and real-time quantitative reverse transcription PCR (qRT-PCR) was used to detect the expression levels of nucleus pulposus cell-associated genes [neural cell adhesion molecule 1 (Ncam-1), aggrecan (Acan), sex-determing region of Y chromosome (SRY)-box transcription factor 9 (Sox9)]. A rat caudal acupuncture intervertebral disc degeneration model was established. Nucleus pulposus cells cultured on different hydrogels were harvested and injected into the degenerated discs separately. Four weeks after surgery, magnetic resonance imaging (MRI) was performed to analyze the water content of the intervertebral discs in each group. Histological tests were performed to examine the disc structure and proteoglycan levels.Results·The elastic modulus of the hydrogels was 1 kPa and 200 kPa when the concentration of GelMA prepolymerisation solution was at 4% and 15% respectively. SEM observation revealed that the hydrogels showed a loose and porous microstructure, and the porosity of hydrogels decreased significantly with the decrease of their stiffness. In vitro experiments demonstrated that both GelMA hydrogel mediums showed good biocompatibility and the ability to support cell proliferation. Nucleus pulposus cells cultured on the soft matrix (4%GelMA) had a lower elongation and spreading area than those cultured on the stiff matrix (15%GelMA), showing a tendency of YAP concentration in the cytoplasm. The gene expression of nucleus pulposus cells was examined and the levels of Sox9, Acan and Ncam-1 in the soft matrix hydrogel group were 23.7, 6.6 and 12.7 times of those in the control group respectively. In vivo experiments on rat disc degeneration showed that the soft hydrogel matrix group had higher disc water content and structural integrity than the stiff hydrogel matrix group.Conclusion·Compared to stiff GelMA hydrogels, hydrogels with low stiffness better maintain the growth phenotypes in the nucleus pulposus cells and have better therapeutic effect on disc degeneration in vivo.